Use of Fish Farming Practices by the Fish Farmers (Research in Agriculture Livestock and Fisheries, 2020)
The main purpose of the study was to determine the extent of use of fish farming practices by the fish farmers. This study was conducted at three unions named Hapania, Kirtipur, and Tilakpur of NaogaonSadarupazilla under Naogaon district. Ninety-two (92) fish farmers were randomly selected as sample from an updated list of 120 fish farmers. Data were collected by a pre-tested interview schedule during 20th September to 20th October 2020. Simple and direct questions with different appropriate scales were used to obtain information. Descriptive statistics and multiple regression analysis was used for the present study. Slightly above half (53.3 percent) of the fish farmers had medium use of fish farming practices, while 42.4 percent fish farmers had high use of fish farming practices, and only 4.3 percent fish farmers had low use of fish farming practices. Thus, overwhelming majority (95.7 percent) of the fish farmers had medium to high use of fish farming practices. Pond size, fish farming experience, cosmopoliteness, and extension contacts of the respondents had significant positive contribution with their use of fish farming practices. Coefficients of other selected variables namely age, education, family size, annual income, and knowledge on fish farming didn’t have any significant contribution with their use of fish farming practices. ‘Lack of government support’ emerged as the 1st ranked problem as per opinion given by the fish farmers (77.17 percent). The least problem as per opinion given by the fish farmers was ‘High labor cost’.Res. Agric., Livest. Fish.7(3): 565-576,  December 2020